Low Molecular Weight Heparin Nebulization Attenuates Acute Lung Injury. (15th May 2017) - Xie, Nianlin; Huan, Menglei; Tian, Feng; Gu, Zhongping; Li, Xiaofei
Abstract : Background. As acute lung injury (ALI) caused high mortality rate, it is important to explore the protection and treatment of ALI. The aim of the current study is to evaluate the effect of low molecular weight heparin (LMWH) nebulization on attenuating acute lung injury and the associated mechanism. Methods. The arterial blood gas, total protein content in bronchoalveolar lavage fluid, lung wet/dry weight ratio, malondialdehyde (MDA) content, superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activity, and Akt phosphorylation were evaluated after the ALI rabbits were treated with or without LMWH nebulization. Results. PaO2 was increased and lung wet/dry weight ratio as well as total protein content in BALF was decreased after LMWH nebulization. After the application of LMWH nebulization therapy, the SOD and GSH-Px activity was rebounded and the increase of MDA content was significantly inhibited. The Akt protein phosphorylation level was decreased after LMWH nebulization therapy. Conclusions. LMWH nebulization treatment can relieve the traumatic ALI in rabbits and inhibit oxidative stress possibly by suppressing the Akt phosphorylation.